(untitled) (Revista Sistemas de Producción Agroecológicos, 2021)
Due to the armed conflict in some of our regions, it was impossible to work in some rural areas with a high potential for a bovine production system. The objective of this project was to promote the farmers, producers, teachers and youth of the Dorado region in the strengthening of the rural sector, through the implementation of good practices in bovine feeding with the livestock of the Educational Institution El Dorado, six blood samples and six samples of fecal material were taken from the animals, soil samples were taken in the paddocks of the farm for physical-chemical analysis, Water samples where the animals consumed for physical-chemical and microbiological analysis. Variables were analyzed using descriptive statistics. Upon clinical examination, body condition was found on average of 3, marked infestation of ectoparasites (ticks and myiasis). The analysis of the blood pictures revealed 5 animals with an increase in the concentration of mean corpuscular hemoglobin, 2 animals with leukocytosis and lymphocytosis, 4 animals with eosinophilia. In blood chemistry, all the animals presented low glucose, high globulins, and a variation in the Ca-P ratio was also found. In the stool 3 animals presented anaplasmosis. The water presented abnormalities in the microbiological parameters. The soils are oxisols, sandy loams, with deficiencies in organic matter, pH and total nitrogen. Improving the quality of water and soil we can have better pastures, improving sanitation, better use of food, and then apply strategies that improve the production of green forage, correct establishment of improved meadows, adequate use of fertilizers and fertilizers, adequate rotation of paddocks, and the establishment of forage conservation methods such as silage and hay.